The Role of Early Pregnancy Serum Adiponectin Level in Predicting Development of Gestational Diabetes Mellitus (GDM) (Journal of Dhaka Medical College, 2025)
Background: Early prediction of GDM by measuring a biomarker at first trimester of pregnancy may prevent maternal and fetal complication. Adiponectin, which modulate insulin sensitivity, is secreted from adipose tissue and decreases blood glucose level. The objective of the study was to evaluate the association of maternal first trimester serum adiponectin with development of GDM.Methodology: This longitudinal study was conducted in the BSMMU, Dhaka from June, 2021 to May, 2022 where pregnant women of first trimester were selected by purposive convenient sampling. At first 94 pregnant women were selected after excluding diabetes or previous history of GDM and their serum adiponectin level was measured. Then the participants were followed up at 24-28 weeks of gestation and OGTT was done to detect GDM. ROC was used to decide the best cut-off point of adiponectin level for detection of GDM. The respondents were divided into ‘below cut-off’ group and ‘above cut-off’ group. Differences between two groups were assessed by statistical test.Results: A total 18 respondents developed GDM from both group. In below cut-off’ group, out of 26 respondents 13 developed GDM and remaining 13 were euglycemic. Whereas in above cut-off group, out of 62 respondents, majority 57 were euglycemic and only 5 women developed GDM. ROC analysis of adiponectin level for detection of GDM, a AUC value 0.887 (95% confidence interval 0.802-0.972) was found which was statistically significant (p